The effects of immunocastration and dried distillers grains with solubles withdrawal on growth performance, carcass characteristics, fatty acid analysis, and iodine value of pork fat depots - M D Asmus; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2012)
A total of 1,360 pigs (PIC 337 × 1050, initially 53.0 lb) were used in a 125-d study to determine the effects of dried distillers grains with solubles (DDGS) withdrawal post-immunocastration (IC; Improvest, Pfizer Animal Health, Kalamazoo, MI) on growth performance and carcass fat quality of growing-finishing pigs. Pens of pigs were randomly allotted by initial weight and gender (barrows or IC) to 1 of 3 dietary treatments with 8 replications per treatment for a total of 48 pens with 27 to 29 pigs per pen. Treatments were arranged in a 2 × 3 factorial with the main effects of gender (barrow or IC) and diet (0% DDGS throughout, 30% DDGS throughout, or 30% DDGS through d 75 then withdrawn to 0% to d 125). Boars were injected with Improvest on d 39 and 74 of the study. Dietary treatments were corn-soybean meal— based diets and fed in 5 phases. No gender × diet interactions (P>0.18) were observed except for a tendency for F/G (P<0.07) during the second phase (d 25 to 53), when 1 of the 2 barrow groups fed 30% DDGS had an increase in ADFI resulting in poorer F/G. For the entire period before the second Improvest injection (d 0 to 74), barrows tended (P<0.08) to have increased ADG (1.98 vs. 1.95 lb) and increased (P<0.001) ADFI (4.32 vs. 3.91 lb) but were less efficient (P<0.001) than boars (2.19 vs. 2.01). During the same time period, pigs fed 30% DDGS had reduced (P<0.002) ADG and poorer feed efficiency.; Swine Day, Manhattan, KS, November 15, 2012
Keywords: Kansas Agricultural Experiment Station contribution; no. 13-026-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1074; Swine; DDGS; Improvest; Finishing pig; Withdrawal